(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Regional economies is a relatively young branch of economics, whose theoretical aspects started to develop in the 20s and 30s of the previous century, but gained vivid manifestation in the EU Regional policy. Since the Rome Treaty (1957), the need for a coordinated community solution to regional problems and the correction of regional imbalances was also recognised in EU political documents. The end of the twentieth century was the beginning of important international political processes marked by the start of a new way of thinking. This new way was sustainable development. Sustainable development is a concept that has to combine economic growth with such a use of natural resources that benefits the society as a whole. The long-term development has three dimensions: environmental, economic and social. In this paper, the attention will be devoted to the influence of these dimensions on the regional development.The aim of this paper is to provide a new viewpoint, as it may seem, related to well-known things that include such economic concepts as regional development and sustainable development and to evaluate sustainable development in Latvian regions. To achieve the aim, the following tasks were selected: to evaluate the theoretical background of regional economy, to examine the main indicators of regional development, and to prepare a regional development forecast. The following research methodology was used: literature review, graphical method, focus group discussions and logically constructive approach – for making judgements and result analysis; synthesis method – to combine the elements in a unified system; social research methods – to obtain the primary information and to carry out its verification. Conclusions: the main reasons for misbalanced regional development are the differences in employment, levels of income and investment. The research proposes solutions to promote balanced regional development.